ChemInform Abstract: Copper‐Catalyzed Direct ortho‐Alkylation of N‐Iminopyridinium Ylides with N‐Tosylhydrazones. Issue 34 (1st August 2013) - Xiao, Qing; Ling, Lin; Ye, Fei; Tan, Renchang; Tian, Leiming; Zhang, Yan; Li, Yuxue; Wang, Jianbo
Abstract The mild operationally simple title reaction proceeds using an inexpensive catalyst without any ligand.